Topology optimization method applied to laminar flow machine rotor design. - Sá, Luís Fernando Nogueira de (2016)
Flow machines are very important to industry, being widely used on various processes. Performance improvements are relevant factors and can be achieved by using optimization methods, such as topology optimization. Thus, this work aims to develop a method to design radial flow machine rotors operating on laminar regime, by implementing a topology optimization formulation based on density model. The design of a rotor involves firstly modelling the fluid flow by using the Navier-Stokes equations on a rotating reference frame and using the Finite Element Method for solving the differential equations. To determine the material distribution on the domain, a porous flow model based on the Darcy equation is employed by using an inverse permeability that interpolates between fluid and solid. In the optimization phase, it is defined a multi-objective function that aims to minimize the viscous energy dissipation, vorticity and power. The optimization problem is implemented using the FEniCS environment and the libraries dolfin-adjoint and pyIpopt. The optimized topologies are verified with the ANSYS software. The resulting topologies are post-processed and a CAD model is created. The rotors are manufactured by using a 3D printer, the complete prototype is built by coupling an electric brushless motor and an experimental characterization is performed by measuring fluid flow and pressure head given by the pumps. Experimental and computational results are compared and the improvement is verified.